2011
DOI: 10.5539/ijb.v3n2p67
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity, Behavioural Changes and Histopathological Effect of Paraquat Dichloride on Tissues of Catfish (Clarias Gariepinus)

Abstract: The toxicity of Paraquat dichloride, a herbicide, was investigated with emphasis on histopathological effects of African Catfish (Clarias gariepinus) juvenile. The fishes were exposed to 0, 20, 60, 80, 110 mg/l of Paraquat dichloride .,The lethal concentration (LC 50 ) value of Paraquat dichloride was 1.75mg/l for 96 h of exposure. Histopathology of the organs after 96 hr exposure revealed cell proliferation, lamellar fusion, lamellar cell hyperplasia, and epithelial lifting. In the liver, there was vacuolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 4 publications
3
22
1
2
Order By: Relevance
“…The observed behavioural changes in C. gariepinus exposed to paraquat in the present study, which indicated internal effects on body physiology, may be attributed to a neurotoxic effect of paraquat. Our results are consistent with previous reports on fish exposed to paraquat [16,32,37], and in other pesticides, such as carbosulfan [38], malathion [39], dichlorvos [40], and chlorpyrifos [41].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed behavioural changes in C. gariepinus exposed to paraquat in the present study, which indicated internal effects on body physiology, may be attributed to a neurotoxic effect of paraquat. Our results are consistent with previous reports on fish exposed to paraquat [16,32,37], and in other pesticides, such as carbosulfan [38], malathion [39], dichlorvos [40], and chlorpyrifos [41].…”
Section: Discussionsupporting
confidence: 83%
“…The sublethal concentrations of paraquat used in our study (1.37 and 2.75 mg/L) are environmentally realistic because environmental concentrations of 0.01 µg/L and 0.14-8.70 µg/L of paraquat have been reported in Elechi Creek, Nigeria [35], and in some water bodies in Thailand [36], respectively. Although our test concentrations exceeded the 0.1 µg/L safety limit established by the United State Environmental Protection Agency [37], considering the repeated application of the pesticide in agricultural fields and other anthropogenic sources, the actual concentration in aquatic environments may exceed this limit. The observed behavioural changes in C. gariepinus exposed to paraquat in the present study, which indicated internal effects on body physiology, may be attributed to a neurotoxic effect of paraquat.…”
Section: Discussionmentioning
confidence: 98%
“…Paraquat merupakan bahan aktif herbisida yang paling toksik (Watts 2010). Paraquat umum digunakan di perkebunan buah, sayur, jagung, padi dan lain-lain untuk mengendalikan gulma pada awal penanaman (Ladipo 2011;Brown et al 2004;Akinloye et al 2011). Di perkebunan kelapa sawit paraquat digunakan untuk pemusnah ilalang (Saragih 2005).…”
Section: Pendahuluanunclassified
“…Sedangkan rumput yang diberi RPP pada kelompok kambing C dan D menunjukkan hiperemia (kelebihan darah pada suatu bagian tubuh) paru dan otak, hidroperikardium (genangan cairan pada area lapisan epikardium jantung), dan erosi pada saluran pencernaan (Tabel 1 dan Gambar 2). Paraquat menghasilkan enzim proteolitik dan radikal bebas yang menyebabkan kerusakan pada organ dan dapat menimbulkan kematian (Cope 2004;Ladipo 2011;El-Sayed danRizk 2009). …”
Section: Hasil Pengamatan Patologi Anatomi (Pa)unclassified
“…Paraquat (PQ), a non‐selective and non‐systemic herbicide with a wide spectrum of activity, has been used for controlling pests of cultivated farmlands of rice, cotton, fruit, potatoes, tea, sugar cane and vegetable. After spraying directly onto leaves, it quickly kills a wide range of annual grasses, broad leafs, weeds and some perennial grasses (Ladipo, Doherty & Oyebadejo ).…”
Section: Introductionmentioning
confidence: 99%